DNA methylation at diagnosis is associated with response to disease-modifying drugs in early rheumatoid arthritis - Glossop, John R.; Nixon, Nicola B.; Emes, Richard D.; Sim, Julius; Packman, Jon C.; Mattey, Derek L.; Farrell, William E.; Fryer, Anthony A. (Future Medicine, 2016)
Aim: A proof-of-concept study to explore whether DNA methylation at first diagnosis is associated with response to disease-modifying antirheumatic drugs (DMARDs) in patients with early rheumatoid arthritis (RA). Patients & methods: DNA methylation was quantified in T-lymphocytes from 46 treatment-naive patients using HumanMethylation450 BeadChips. Treatment response was determined in 6 months using the European League Against Rheumatism (EULAR) response criteria. Results: Initial filtering identified 21 cytosine-phosphate-guanines (CpGs) that were differentially methylated between responders and nonresponders. After conservative adjustment for multiple testing, six sites remained statistically significant, of which four showed high sensitivity and/or specificity (≥75%) for response to treatment. Moreover, methylation at two sites in combination was the strongest factor associated with response (80.0% sensitivity, 90.9% specificity, AUC 0.85). Conclusion: DNA methylation at diagnosis is associated with disease-modifying antirheumatic drug treatment response in early RA.